MENYIKAT GIGI TEKNIK ROLL DAN SCRUB TERHADAP SKOR PLAK PASIEN PEMAKAI ALAT ORTODONTI CEKAT DI KLINIK GIGI - Eliza da Cruz; Siti Sulastri; Dwi Eni Purwati (Journal of Oral Health Care, 2014)
Background The prevalence (incidence) maxillary anteriortooth arrangement abnormalities in Indonesia is still at80%. Component has a fixed orthodontic shape that facilitateattachment of plaque rumuit longer and can increasethe risk of caries, gingivities, and periodontal disease islikely to occur. One of prevention efforts were made toprevent the problem is to control dental plaque. Among theassortment of plaque control, technique more simple, safeand effective tooth brushing. Efectifities toothbrushing dependson several things, namely the shape of a toothbrush,fekwensi, duration of brushing your teeth and themost important is brushing techniques. Definding brushingtechnique should be considered in order to achievehygiene and oral health, especially for fixed orthodonticwearers. In this study, brushing technique is the techniqueused to roll danteknik scrubs because both techniquesare the most commonly used technique in general. Objectiveto determine the effect of tooth brushing technique rolland technique scrub against plaque scores of patientsusing fixed orthodontic tools in Ibnu Sina Dental clinic.Result showing that after brushing with roll technique after2 minutes, the average plaque score dropped from 20.13to 6.07. Meanwhile, after brushing with a scrub technique,the average plaque score dropped from 24.00 into 11.47.From the analysis of the Wilcoxon on roll tooth brushingtechnique that z-hitung 3, 272 (sig 0.001 < 0.05) and ontooth brushing techniques scrub showed that z hitung -3.578 (sig 0.000 < 0.05). Contained significant effect betweenroll teeth brushing technique agains the plaquescores of patients on fixed orthodontic appliance (p: 0.000)and a significant influence between scrub teeth brushingtechnique against plaque scores in patients with fixed orthodonticwearers (p:0.000). Conclusion Roll and scrub teethbrushing techniques effectively/greatest decrease plaquescores of patients using fixed orthodontic tools in IbnuSina Dental clinic, Yogyakarta (p = 0.000).